Deterministic modelling of whole-body sheep metabolism - Smith, Emma Catherine (Curtin University, 2014)
Livestock is amongst Australia’s most enduring and prolific industries; however whole-body modelling approaches are limited in livestock research. Mathematical techniques are employed, extending an existing lamb growth model to adulthood. It tracks wool, protein, fat, metabolites and DNA pools, simulating whole-body metabolism. Implementation into a dynamic optimisation package allows for the optimisation of model parameters to improve model behaviour. The focus is on feed, nutrient absorption, energy expenditure, wool growth and defining appropriate initial conditions.